MANAGERIAL ACCOUNTING ISSUES IN MSMES IN KOLAKA REGENCY: A PHENOMENOLOGICAL QUALITATIVE APPROACH - Abd. Haris Rahim; Anshar (PT. Radja Intercontinental Publishing, 2026)
This study aims to identify and analyze managerial accounting problems faced by Micro, Small, and Medium Enterprises (MSMEs) in Kolaka Regency, Southeast Sulawesi. This study uses a qualitative approach with phenomenological methods. Data collection was conducted through in-depth interviews with 12 informants consisting of MSME actors in various sectors, participatory observation, and documentation. Data analysis techniques use the Miles, Huberman, and Saldaña (2014) model which includes data condensation, data display, and conclusion drawing. The results identified six main themes of managerial accounting problems, namely: (1) mixing of personal and business finances, (2) absence of production cost recording systems, (3) absence of planning and budgeting, (4) selling price determination without calculation basis, (5) minimal utilization of accounting information in decision making, and (6) weak business performance evaluation. This study recommends the need for local wisdom-based managerial accounting assistance programs involving local government, universities, and local business communities.